Haloperidol and Risperidone Induce Apoptosis Neuronal Cell: In vivo Study - Ester G Panserga; Cecep S Kristanto; Budi Pratiti; Patricia Wulandari (HM Publisher, 2020)
Introduction: Antipsychotics are drugs that are widely prescribed for mental disorders, such as schizophrenia and psychosis. Recent in vitro studies show antipsychotics play a role in the initiation of neuronal cell apoptosis. This study aims to determine the effect of haloperidol and risperidone on neuronal cell apoptosis in Wistar white rats. Methods: Male Wistar rats aged 8 weeks (n = 30) were used in this study. Wistar rats were randomized into 6 groups. Group A: 5 Wistar rats as the control without induced schizophrenia, aquadest, and drugs. Group B: 5 Wistar-induced psychotic mice (using 30 mg / kgBB ketamine, intraperitoneal injection for 5 days) and aquadest. Group C: 5 rats were induced psychotic and were given haloperidol or 0.05 mg / kgBB orally, for 28 days. Group D: 5 mice were induced psychotic and were given haloperidol 0.1 mg/kg orally, for 28 days. Group E: 5 mice were induced psychotic and were given risperidone 0.05 mg / kgBB orally, for 28 days. Group F: 5 mice were induced psychotic and given risperidone 0.1 mg / kgBB orally, for 28 days. Apoptosis of neuronal cells in the ventral tegmental area was assessed by caspase-3 immunohistochemistry. The colored area will be calculated as a total percentage using the ImageJ program. Results: Risperidone and haloperidol increase caspase-3 activity, but haloperidol increases caspase- 3 activity more than risperidone. Conclusion: Risperidone and haloperidol induce apoptosis of neuronal cells and tardive dyskinesia in Wistar rats with psychotic models.